Frailty assessment in geriatric trauma patients: comparing the predictive value of the full and a condensed version of the Fried frailty phenotype - Joninah Braunschweig; Wei Lang; Gregor Freystätter; Christian Hierholzer; Heike A. Bischoff-Ferrari; Michael Gagesch (BMC Geriatrics, 2024)
Abstract Background Frailty is associated with multiple negative outcomes in geriatric trauma patients. Simultaneously, frailty assessment including physical measurements for weakness (grip strength) and slowness (gait speed) poses challenges in this vulnerable patient group. We aimed to compare the full 5-component Fried Frailty Phenotype (fFP) and a condensed model (cFP) without physical measurements, with regard to predicting hospital length of stay (LOS) and discharge disposition (DD). Methods Prospective cohort study in patients aged 70 years and older at a level I trauma center undergoing frailty assessment by 5-component fFP (fatigue, low activity level, weight loss, weakness, and slowness). For the cFP, only fatigue, low activity level and weight loss were included. Co-primary outcomes were LOS and DD. Results In 233 of 366 patients, information on all 5 frailty components was available (mean age 81.0 years [SD 6.7], 57.8% women) and included in our comparative analysis. Frailty prevalence was 25.1% and 3.1% by fFP and cFP, respectively. LOS did not differ significantly between frail and non-frail patients, neither using the fFP (p = .245) nor the cFP (p = .97). By the fFP, frail patients were 94% less likely to be discharged home independently (OR 0.06; 95% CI 0.007-0.50, p = .0097), while using cFP, none of the frail patients were discharged home independently. Conclusion The fFP appears superior in identifying frail trauma patients and predicting their discharge destination compared with the condensed version. LOS in this vulnerable patient group did not differ by either frailty phenotype even if compared with those identified as non-frail.